Precipitation and Economic Growth - Michael Berlemann; Daniela Wenzel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
As the ongoing process of global warming goes along with changes in both mean precipitation and precipitation extremes, the scientific interest in the effects of rainfall on economic prosperity has recently grown significantly. However, the few existing empirical studies of short-run growth effects of precipitation deliver inconclusive results. The medium- and long-run growth perspective is yet mostly unexplored. In this paper we deliver a systematic analysis of the short- and long-run growth effects of rainfall based on a large panel dataset covering more than 150 countries over the period of 1950 to 2014. We find strong and highly robust empirical evidence for long-lasting negative growth effects of rainfall shortages in poor and underdeveloped countries, which are not driven by the subsample of Sub Saharan African countries.
Keywords: O44; 330; Economic Growth; Precipitation